EARLY OUTCOMES OF SURGICAL INTERVENTION IN PATIENTS WITH MOTOR VEHICLE INDUCED ACUTE SUBDURAL AND EXTRADURAL HEMATOMA (Journal of Medical & Health Sciences Review, 2025)
Introduction: Acute subdural and extradural hematomas (SDH and EDH) are common traumatic brain injuries resulting from motor vehicle accidents. Prompt surgical intervention is often required, but the early outcomes and long-term rehabilitation needs of these patients remain a significant area of concern. This study evaluates the early outcomes of surgical interventions in patients with motor vehicle-induced acute SDH and EDH and identifies delayed detrimental presentations that affect rehabilitation. Objective: The primary aim of this study was to assess the early outcomes of surgical intervention in patients with motor vehicle-induced acute SDH and EDH. A secondary objective was to identify delayed detrimental presentations in hospital, specifically focusing on rehabilitation needs. Methodology: This cross-sectional study included a sample of 60 patients with acute SDH or EDH who underwent surgical intervention following a motor vehicle accident. The sample size was determined based on the anticipated frequency of these injuries, with data collected and analyzed using Open-Epi. Results and Findings: Early outcomes were assessed in terms of survival, neurological recovery, and post-surgical complications. Rehabilitation challenges were also documented, focusing on cognitive, motor, and functional impairments that developed during hospitalization. The study found that the majority of patients experienced significant improvement in neurological function following surgery. However, a notable proportion of patients presented with delayed complications, including cognitive deficits, motor impairments, and the need for extended rehabilitation. These delayed presentations were associated with longer hospital stays and more intensive post-surgical therapy. Conclusion: Surgical intervention in patients with motor vehicle-induced acute SDH and EDH generally leads to favorable early outcomes. However, delayed complications affecting rehabilitation were common and highlight the importance of ongoing monitoring and tailored rehabilitation strategies to optimize long-term recovery. Further research is necessary to develop predictive models for identifying patients at higher risk of delayed complications to improve post-surgical care and rehabilitation outcomes.